EDEN ISS - Greenhouse in Antarctica - Vrakking, Vincent; Schubert, Daniel; Zabel, Paul; Zeidler, Conrad; Dorn, Markus; Ferl, Robert; Paul, Anna-Lisa (2021)
Ant-Land Status Report describing activities and preliminary results of the 2020 Antarctic winter season and the 2020/21 Antarctic summer season